10-year results following impaction bone grafting of major bone defects in 29 rotational and hinged knee revision arthroplasties. (August 2013) - Hilgen, Verena; Citak, Mustafa; Vettorazzi, Eik; Haasper, Carl; Day, Kimberly; Amling, Michael; Gehrke, Thorsten; Gebauer, Matthias
<x xml:space="preserve">Abstract</x> Background and purpose — Substantial bone loss in revision total knee arthroplasty (TKA) is a challenging problem. We studied whether impaction bone grafting provides long-term restoration of bone stock in the treatment of major bone defects in revision surgery of rotational and hinged knee arthroplasties (LINK Endo-Model). Patients and methods — Between 1996 and 2006, 29 knees in 29 patients underwent revision procedures of rotational and hinged knee arthroplasties using impaction bone grafting (IBG) to reconstruct major bone defects. At the latest follow-up, the clinical examination included the Knee Society score (KSS), standardized radiographs, and a questionnaire for the WOMAC score. Results — After a mean follow-up of 10 (6–13) years, 14 knees with 19 IBG reconstructions (5 total, 9 partial revisions) had failed. 12 knees were treated with re-revision surgery mean 5 (1–12) years after the first revision, due to mechanical failure and aseptic loosening of the components. In all these failed cases, the surgeon observed a lack of incorporation with bone graft resorption in the femur or tibia during the re-revision procedure. In all 15 knees that were not re-revised, with 21 reconstructions (6 total, 9 partial revisions), an improvement in the combined KSS score (knee score + function score) of 60 points (p < 0.001) was found at the latest follow-up. In 12 of these knees, a clear incorporation with no visible radiolucent lines around the component and no sign of substantial graft resorption was noted, while unclear radiographic graft incorporation was seen in 3 knees. Interpretation — Our results clearly indicate that IBG alone is not a methodologically sound technique in the revision of rotational and hinged knee arthroplasties.